Modeling of human behavior in crowds using a cognitive feedback approach. (July 2017) - Papelis, YE; Kady, RA; Bair, LJ; Weisel, E
We present an agent-based approach to modeling crowd behavior that is based on complementary psychological and engineering principles. The application focus is for developing realistic models that address not only the physical but also the psychological aspects of crowd behavior. Our approach to modeling the psychology of a crowd is based on the principle of emotional reflection. According to this principle, human emotions are evoked in response to the perception of other people's emotions, implying that emotions propagate in a crowd as a result of each person's perception of other crowd members' emotions in addition to external factors. We demonstrate that when incorporating an emotional component into a crowd simulation, there is enough sensitivity between the outcomes and emotion-based responses to provide a rich and powerful test-bed for assessing possible effects of emotionally driven responses in crowds. The emotional model is coupled with a movement model that is based on the social forces formulation, but with parameters that vary according to the current emotional state of each crowd member. We present the model along with results of how different emotional levels can affect the movement dynamics of crowds.